Hubungan Pola Makan Terhadap Kejadian Hipertensi di Wilayah Kerja Puskesmas Kebun Sikolos Kota Padang Panjang Tahun 2019 - Abdi Iswahyudi Yasril; Widya Rahmadani (Jurnal Sehat Mandiri, 2020)
Hypertension is a non-communicable disease. This continues to increase from year to year, and can lead to various other chronic diseases. This study aims to analyze the effect of diet on hypertension in 2019. This type of research is an observational analytic study with a prospective cohort study design. The population in this study were all adults (26 - 45 years) at the Puskesmas Kebun Sikolos. By means of purposive random sampling, a sample of 110 respondents was selected. The data obtained were processed by computerization using the Chi-square test and the Mantel Haenszel test. Chi-square test results showed that there was a relationship between salt consumption (p = 0.004 and RR = 1.521), fat (p = 0.008 and RR = 1.464), fiber (p = 0.014 and RR = 2.047) and caffeine (p = 0.012 and RR = 1.438) against hypertension. The coat-Haenszel test results showed that age, gender, family history, physical activity, smoking habits, and obesity were confounding factors in the relationship between diet and hypertension. It can be concluded that the main factor that is closely related to hypertension is salt consumption. It is advisable to provide an understanding to the public about the risk of frequent salt consumption which causes hypertension to be very beneficial